Fluconazole and cinnamaldehyde loaded-multilayer elektrospun nanofibers for the treatment of fungal keratitis - CESUR, SÜMEYYE; OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (My University, 2022)
Inflammation of the cornea due to physical, chemical and infectious causes is known as keratitis[1]. Fungi are one of the most challenging species to diagnose and treat among the organisms that cause keratitis. Moreover, fungal keratitis has been proven to be more virulent and destructive than keratitis caused by bacterias[2]. In this study, two-layer polyvinyl alcohol and gelatin (PVA/GEL) nanofibers loaded with different biological agents, which accelerate wound closure by suppressing the disadvantages of traditional methods in the treatment of fungal keratitis, were produced by the electrospinning method. Cinnamaldehyde (CA), an FDA-approved volatile molecule found in cinnamon essential oil, and fluconazole (FLU), an antifungal drug, were incorporated into PVA/GEL nanofibers to inhibit the growth and biofilm formation of Candida albicans, one of the pathogens that cause fungal keratitis. The morphology, and chemical structures of the produced pure (PVA/GEL), FLU loaded (PVA/GEL/FLU), CA loaded (PVA/GEL/CA), and combined FLU and CA loaded (PVA/GEL/COM) nanofibers were analysed by scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FT-IR), respectively. The mechanical analysis and drug release kinetics of the nanofibers were investigated. PVA/GEL/FLU, PVA/GEL/CA and PVA/GEL/FLU/COM nanofibers were evaluated for their antifungal and antibiofilm activity against Candida albicans. Results showed that PVA/GEL/FLU and PVA/GEL/COM nanofibers have significant antifungal activity and inhibited biofilm formation by 37% and 49%, respectively. The originality of this study lays in the design of the multilayer electrospun nanofibers, which are loaded with both biofilm inhibitor agent and an antifungal drug. This kind of construct can be utilised in the treatment of fungal keratitis and to produce patches that accelerate wound healing and allow controlled release of the bio-active agents.
Keywords: Sağlık Bilimleri; Mühendislik ve Teknoloji; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Clinical Medicine (MED); Engineering, Computing & Technology (ENG); Fungal Keratitis; Nanofiber; Fluconazole; Cinnamaldehyde; Cornea Tissue Engineering